2007
DOI: 10.1152/japplphysiol.01281.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output and leg and arm blood flow during incremental exercise to exhaustion on the cycle ergometer

Abstract: To determine central and peripheral hemodynamic responses to upright leg cycling exercise, nine physically active men underwent measurements of arterial blood pressure and gases, as well as femoral and subclavian vein blood flows and gases during incremental exercise to exhaustion (Wmax). Cardiac output (CO) and leg blood flow (BF) increased in parallel with exercise intensity. In contrast, arm BF remained at 0.8 l/min during submaximal exercise, increasing to 1.2 +/- 0.2 l/min at maximal exercise (P < 0.05) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 63 publications
10
126
1
Order By: Relevance
“…In fact, in our experiments stroke volume increased significantly when transitioning from rest to 69% peak power, but was the same at 69, 77, and 85% peak power. These findings are in line with those of Calbet et al (2007), who reported stroke volume to rise after the transition from unloaded pedalling to submaximal exercise, and then reach maximal values beyond 64% peak power. Furthermore, our data confirm the findings of Davies et al (1972), who found stroke volume to be similar between 40 and 80% of maximal aerobic power.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, in our experiments stroke volume increased significantly when transitioning from rest to 69% peak power, but was the same at 69, 77, and 85% peak power. These findings are in line with those of Calbet et al (2007), who reported stroke volume to rise after the transition from unloaded pedalling to submaximal exercise, and then reach maximal values beyond 64% peak power. Furthermore, our data confirm the findings of Davies et al (1972), who found stroke volume to be similar between 40 and 80% of maximal aerobic power.…”
Section: Discussionsupporting
confidence: 92%
“…Although potentially complicated by the small versus large muscle mass approach in these two studies, this is not the first time that arm-and leg-specific differences have been found in terms of metabolic and vascular responses (4,5,24,25,45). Recent work, investigating limb-specific regulation of blood flow during incremental arm or leg exercise, revealed that for a given local V O 2 , leg vascular conductance was five to six times greater than arm vascular conductance (4).…”
Section: Discussionmentioning
confidence: 87%
“…Details of the experimental protocols used in study 1 have been reported (Calbet et al . 2007; Boushel et al . 2011; Helge et al .…”
Section: Methodsmentioning
confidence: 99%